PhD Abstracts - HUTTON, GRAHAM (Journal of functional programming, 2019)
Many students complete PhDs in functional programming each year. As a service to the community, twice per year the Journal of Functional Programming publishes the abstracts from PhD dissertations completed during the previous year.